Pengaruh sistem pengendalian internal, ketaatan aturan dan kesesuaian kompensasi terhadap kecenderungan kecurangan akuntansi - Himawan Wibisono, Sukarno; As’adi, As’adi; Mukoffi, Ahmad; Narsi, Yunita (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2025)
The purpose of this study is to determine the influence of the internal control system, compliance with rules and the suitability of compensation on the tendency of accounting fraud in SOEs listed on the IDX partially. The research was conducted based on quantitative methods. The determination of this research sample uses the purposive sampling method so that a research sample of 6 SOEs listed on the IDX was obtained. This research data uses the financial statements of state-owned companies for the 2020-2024 period. The data analysis method used is multiple linear regression. The results of the study prove that the internal control system has a significant effect on the tendency of accounting fraud with t count = 4,574, compliance with rules has a significant effect on the tendency of accounting fraud with t count = 4,200 and the suitability of compensation has a significant effect on the tendency of accounting fraud with t count = 4,163. These results prove that the existence of an internal control system, compliance with rules and the suitability of compensation are able to reduce the tendency of accounting fraud in SOE companies